Pengaruh Pertumbuhan Penduduk dan Tingkat Pendidikan terhadap Tingkat Kemiskinan di Kabupaten Aceh Selatan - Rahmi Yanti; Alisman Alisman; , Yenny Ertika (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
No matter where they are in the world, the government always seems to be worried about poverty. The issue of extreme poverty permeates all sectors of the economy, which is sometimes the fulcrum of the success of state governments, especially in developing countries. Knowing how changes in population and educational attainment affect poverty rates in South Aceh Regency is the driving force for this study. With poverty rate (Y) and population growth and education level (X) as independent variables in the multivariate linear regression model, this study draws its conclusions. The poverty rate in South Aceh Regency is greatly influenced by the findings of partial testing of factors related to the increase in the population. Based on the findings of the partial education level exam, the poverty rate in South Aceh Regency is affected. The findings from population and education level testing at the same time have a major impact on poverty rates. There is a strong correlation between the rate of population growth and the level of education in South Aceh Regency and the poverty rate.